High-fat diet impairs microbial metabolite production and aggravates influenza A infection - Franziska Hornung; Harini K. SureshKumar; Laura Klement; Yasmina Reisser; Christoph Wernike; Vivien Nischang; Paul M. Jordan; Oliver Werz; Carsten Hoffmann; Bettina Löffler; Stefanie Deinhardt-Emmer (Cell Communication and Signaling)
Abstract Background Alterations in the gut microbiom can significantly impact various regions in the human body, including the pulmonary tract. This study investigates alterations in the gut microbiome during a high-fat diet (HFD), particularly short-chain fatty acids (SCFAs), and how these metabolites affect lung infection caused by Influenza A virus (IAV). Methods We used a HFD-mouse model to evaluate gut microbiota composition, SCFA levels, and pulmonary outcomes following IAV infection. Microbial changes were analyzed via taxonomic and functional profiling and SCFA levels were measured from non-obese and obese serum donors. Ultimately, acetate’s effects were tested ex vivo in human precision-cut lung slices (PCLS) and in vitro in pulmonary epithelial cells. Mechanistic studies investigated the involvement of the SCFA receptor free fatty acid receptor 2 (FFAR2) and intracellular antiviral pathways. Results Our data indicates an increased Firmicutes/Bacteroidetes ratio of the gut microbiome and an altered carbohydrate metabolism, leading to reduced SCFA production. Infected HFD mice showed increased IAV titers and sustained microbial alterations. Interestingly, acetate demonstrated antiviral effects in both the human PCLS model and pulmonary cells with an reduced viral replication. These effects depended on FFAR2, which also acts as an IAV co-receptor, as acetate treatment led to FFAR2 internalization and influenced host cell metabolism in our in vitro data. Conclusion HFD alters the SCFA production, reducing acetate levels in the gut microbiome. This reduction may lead to higher viral loads and worsened disease in HFD mice infected with IAV. Our findings indicate that acetate has antiviral effects during IAV infection in both a human ex vivo lung model and pulmonary epithelial cells. Here, acetate prevents viral entry and affects the cellular metabolic state and antiviral response. Understanding these mechanisms could provide new targets for preventing and treating viral infections in individuals with diet-related health issues. Graphical Abstract